2019
DOI: 10.1080/21691401.2019.1626412
|View full text |Cite
|
Sign up to set email alerts
|

Anticarcinogenic potential of gold nanoparticles synthesized from Trichosanthes kirilowii in colon cancer cells through the induction of apoptotic pathway

Abstract: Gold nanoparticles (AuNPs) is the most excellent anticancer theranostic nanoparticles synthesized through efficient, simple and green synthesis method using extracts of Trichosanthes kirilowii, extensively characterized by UV-spectroscopy, FT-IR and TEM techniques. The AuNPs, synthesized by means of T. kirilowii extracts identified that nanoparticles were $50 nm in size, which is an admirable nano dimension attained by green synthesis. In agreement with the outcome of microscopic cellular morphological observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…Despite numerous studies suggesting the biocompatibility of AuNPs, the anticancer activity of some green synthesized AuNPs was confirmed. As an example, AuNPs synthesized with Trichosanthes kirilowii caused cell cycle arrest in G 0 /G 1 phase and induced apoptosis via activating several apoptotic pathways, involving bid, bax/bcl2 and caspases in colon cancer cells [121]. Similar activities were observed on A549 cells and on HepG2 hepatocellular carcinoma cells treated with green synthesized AuNPs prepared by using Marsdenia tenacissima plant extract [122] and AuNPs synthesized with Cordyceps militaris mushroom extract [11], respectively.…”
Section: Toxicity and Anticancer Activity Of Green Synthesized Aunps mentioning
confidence: 58%
“…Despite numerous studies suggesting the biocompatibility of AuNPs, the anticancer activity of some green synthesized AuNPs was confirmed. As an example, AuNPs synthesized with Trichosanthes kirilowii caused cell cycle arrest in G 0 /G 1 phase and induced apoptosis via activating several apoptotic pathways, involving bid, bax/bcl2 and caspases in colon cancer cells [121]. Similar activities were observed on A549 cells and on HepG2 hepatocellular carcinoma cells treated with green synthesized AuNPs prepared by using Marsdenia tenacissima plant extract [122] and AuNPs synthesized with Cordyceps militaris mushroom extract [11], respectively.…”
Section: Toxicity and Anticancer Activity Of Green Synthesized Aunps mentioning
confidence: 58%
“…[84] Similarly, some earlier studies have shown that mitochondrial membrane disruption caused by AuNPs plays a central role in cell death/apoptosis. [85][86][87] Cui et al [88] stated that the exposure of nanoparticles had increased the rates of ROS production, which eventually reduced the mitochondrial membrane potential leading to cell death. The present research was consistent with the above results and implies the definite potential of Pa-AuNPs to cause apoptosis by depolarization and sensitization of the mitochondrial membrane potential.…”
Section: Assessment Of Mitochondrial Membrane Potential (δψM)mentioning
confidence: 99%
“…Recently, the multiple pathways adjuvanted by AuNPs in colon cancer cells, leading to the apoptosis of tumor cells, have been elucidated. AuNPs enhance reactive oxygen species (ROS) generation, damage mitochondrial membrane, induce G0/G1 phase cell-cycle arrest, and activate caspase expression, ending with apoptosis cell death [67]. An in-vitro study on gold nanoparticles obtained by green synthesis using Trichosanthes kirilowii extracts gave evidence that gold nanoparticles, 50 nm in size, show effective, selective, and anticarcinogenic effects on HCT-116 cells in a dose-dependent manner.…”
Section: Colon Cancermentioning
confidence: 99%
“…The gold nanoparticles significantly enhanced ROS generation, caused mitochondrial damage, and induced G0/G1 phase cell-cycle arrest. Moreover, gold nanoparticle treatment activated caspase expression, inducing apoptosis of tumor cells and showing a highly efficient potential for cancer treatment [67].…”
Section: Colon Cancermentioning
confidence: 99%